Menilai Tingkat Kesehatan Bank dengan Analisis Metode Risk Profile, Good Corporate Governance, Earnings, Capital pada pada Bank Syariah di Indonesia - Hendra Galuh Febrianto; Amalia Indah Fitriana (Banque Syar'i : Jurnal llmiah Perbankan Syariah, 2021)
In the banking world of soundness, banks are very important for the formation of trust. Trust and loyalty to banks is a very helpful factor and makes it easier for bank management to develop good business strategies. Bank Soundness Levels are results issued by banks which are carried out on bank risk and performance (Bank Indonesia Regulation Number: 13/1 / PBI / 2011). If more than conventional banking with Islamic banking, conventional banking finance is better than Islamic banking. This is blessed with poor sharia banking (corporate governance) management. In order to be able to carry out its functions properly, banks must have sufficient capital, ensure the quality of their assets properly, be well managed and managed based on the principle of prudence, generate sufficient profits to maintain an increase, and support liquidity so that it can be adjusted to their needs. Therefore banks are required to be able to achieve and maintain a good and optimal level of performance, because the level of bank performance can increase the level of trust and loyalty needed by the wider community to use the products, services and financial activities of the bank. The purpose of this study is for advanced financial research with analysis of Risk Profiles (Risk Profiles), Good Corporate Governance (GCG), Profitability (Income), and Capital (Capital) which is hereinafter abbreviated as RGEC with the final aim of research for the needs of Sharia banking management in accordance with the latest Bank Indonesia and OJK regulations. This type of research uses descriptive research proposed in the RGEC analysis (Risk Profile, Good Corporate Governance, Income, and Capital) at Islamic Banks in Indonesia. from 2013 to 2017